Engineering cellular systems: modify, repair, but not at all costs. Which ethical benchmarks? - Thiel, Marie-Jo (Medicina e Morale, 2023)
This contribution examines the engineering of molecular and cellular system from an ethical point of view. It is possible today to modify, repair, and treat (…) but it must not be at all costs. Fascination must not blind us to the ethical issues at stake. In order to take on these challenges, the author proposes five sets of intertwined principles suggesting systematic and systemic levels of reasoning. The first set concerns recognition of a free, dignified, autonomous but also vulnerable human being who is at the centre of the ethical approach. A second set aims at the usefulness and reliability of the implemented engineering. Linked to the first two sets, the third one points to the place of information and education, assuming the uncertainties inherent in all human knowledge and the rapid evolution of cellular and molecular engineering techniques and their repercussions on the whole of society. A fourth set refers to social and societal values: justice, equal access to care, non-discrimination, cost of treatment and solidarity... and in addition: cultural and religious perspectives which can sometimes be brakes, sometimes accelerators... The last principle brings these different ethical issues together by stressing the obligation to take a global view: integrating time and space, and the opened prospects and their implications at the anthropological, social and societal, political, environmental, economic, cultural and religious levels.